Phased implementation of spaced clinic visits for stable HIV‐positive patients in Rwanda to support Treat All. (21st July 2017) - Nsanzimana, Sabin; Remera, Eric; Ribakare, Muhayimpundu; Burns, Tracy; Dludlu, Sibongile; Mills, Edward J; Condo, Jeanine; Bucher, Heiner C; Ford, Nathan
Abstract: Introduction : In 2016, Rwanda implemented "Treat All, " requiring the national HIV programme to increase antiretroviral (ART) treatment coverage to all people living with HIV. Approximately half of the 164, 262 patients on ART have been on treatment for more than five years, and long‐term retention of patients in care is an increasing concern. To address these challenges, the Ministry of Health has introduced a differentiated service delivery approach to reduce the frequency of clinical visits and medication dispensing for eligible patients. This article draws on key policy documents and the views of technical experts involved in policy development to describe the process of implementation of differentiated service delivery in Rwanda. Discussion : Implementation of differentiated service delivery followed a phased approach to ensure that all steps are clearly defined and agreed by all partners. Key steps included: definition of scope, including defining which patients were eligible for transition to the new model; definition of the key model components; preparation for patient enrolment; considerations for special patient groups; engagement of implementing partners; securing political and financial support; forecasting drug supply; revision, dissemination and implementation of ART guidelines; and monitoring and evaluation. Conclusions : Based on the outcomes of the evaluation of the new service delivery model, the Ministry of Health will review and strategically reduce costs to the national HIV program and to the patient by exploring and implementing adjustments to the service delivery model.